2004
DOI: 10.1086/422204
|View full text |Cite
|
Sign up to set email alerts
|

Large Species Shifts Triggered by Small Forces

Abstract: Changes in species composition of communities seem to proceed gradually at first sight, but remarkably rapid shifts are known to occur. Although disrupting disturbances seem an obvious explanation for such shifts, evidence for large disturbances is not always apparent. Here we show that complex communities tend to move through occasional catastrophic shifts in response to gradual environmental change or evolution. This tendency is caused by multiple attractors that may exist in such systems. We show that alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(68 citation statements)
references
References 62 publications
1
67
0
Order By: Relevance
“…The model is based on a straightforward multi-species version of the classic Rosenzweig-MacArthur predator-prey model (Rosenzweig & MacArthur 1963;Vandermeer 1993;van Nes & Scheffer 2004), extended with seasonal forcing Scheffer et al 1997). In our interpretation, the model represents a plankton community, although our findings can probably be generalized to other multi-species communities in which organisms have fast growth rates and short generation times compared with the length of the growing season (e.g.…”
Section: Methods (A) Model Descriptionmentioning
confidence: 95%
See 1 more Smart Citation
“…The model is based on a straightforward multi-species version of the classic Rosenzweig-MacArthur predator-prey model (Rosenzweig & MacArthur 1963;Vandermeer 1993;van Nes & Scheffer 2004), extended with seasonal forcing Scheffer et al 1997). In our interpretation, the model represents a plankton community, although our findings can probably be generalized to other multi-species communities in which organisms have fast growth rates and short generation times compared with the length of the growing season (e.g.…”
Section: Methods (A) Model Descriptionmentioning
confidence: 95%
“…The phytoplankton species are consumed by zooplankton species, as described by a multi-species functional response (of Holling type II) with a fixed half-saturation constant H k and maximum grazing rate g k . Selective predation (Chesson 1978) is introduced through the selectivity coefficient S ik of zooplankton species k for phytoplankton species i and it can take values between 0 and 1, indicating the preference of the predator for its prey (van Nes & Scheffer 2004). The factor u accounts for small levels of immigration and is introduced to reduce the probability of heteroclinic cycles.…”
Section: Methods (A) Model Descriptionmentioning
confidence: 99%
“…Disturbance by agricultural activities may reduce the resilience of a high-diversity stable state, increasing the likelihood that the system will cross a critical threshold into a low-diversity self-reinforcing stable state (van Nes and Scheffer 2004, Downing et al 2012, T€ or€ ok et al 2018. Some research has shown how the recovery of abandoned fields may be possible (Meiners et al 2002, Hermy andVerheyen 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Simple ecological models have offered unique insights and general rules regarding the long-term dynamics of many complex systems (May 1976, Tilman 1982, Leibold 1996, Holt and Polis 1997, van Nes and Scheffer 2004, Loreau 2010, Kylafis and Loreau 2011. We build on previous ecological theory considering omnivory (Holt and Polis 1997) and niches (Leibold 1996, Kylafis andLoreau 2011) to explore the cascading effects, long-term consequences, and limits of human niche construction.…”
Section: Introductionmentioning
confidence: 99%